2007
DOI: 10.1038/sj.ki.5002451
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels and early mortality among incident hemodialysis patients

Abstract: Vitamin D deficiency is associated with cardiovascular disease, the most common cause of mortality in hemodialysis patients. To investigate the relation between blood levels of 25-hydroxyvitamin D (25D) and 1,25-dihydroxyvitamin D (1,25D) with hemodialysis outcomes, we measured baseline vitamin D levels in a cross-sectional analysis of 825 consecutive patients from within a prospective cohort of incident US hemodialysis patients. Of these patients, 78% were considered vitamin D deficient with 18% considered se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
581
9
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 727 publications
(643 citation statements)
references
References 54 publications
37
581
9
16
Order By: Relevance
“…Wolf et al showed that among incident haemodialysis patients, those with 25(OH)D levels < 10 ng/mL (25 nmol/L) were at increased risk of 90 day mortality, compared with subjects with 25(OH)D > 30 ng/mL (75 nmol/L). The risk for cardiovascular‐related mortality was also higher for patients with 25(OH)D between 10 to 30 ng/mL (25 to 75 nmol/L) 168. Similar data have been reported for non‐dialysis patients in two prospective studies of small sample size 169, 170.…”
Section: Controversies In the Definition Of Vitamin D Insufficiency Isupporting
confidence: 79%
“…Wolf et al showed that among incident haemodialysis patients, those with 25(OH)D levels < 10 ng/mL (25 nmol/L) were at increased risk of 90 day mortality, compared with subjects with 25(OH)D > 30 ng/mL (75 nmol/L). The risk for cardiovascular‐related mortality was also higher for patients with 25(OH)D between 10 to 30 ng/mL (25 to 75 nmol/L) 168. Similar data have been reported for non‐dialysis patients in two prospective studies of small sample size 169, 170.…”
Section: Controversies In the Definition Of Vitamin D Insufficiency Isupporting
confidence: 79%
“…Studies in dialysis patients as well as in renal transplant recipients have demonstrated the strong association of CVE history with CAC, the latter most likely related to atherosclerosis (23,24,25,19) (30). Observational studies already showed that vitamin D deficiency is associated with increased risks for cardiovascular disease and death in the general population (31,32), with heart failure in patients referred for coronary angiography (33) and with mortality in hemodialysis and CKD patients (34,35). Moreover low 25-(OH) vitamin D3 levels are associated with traditional atherosclerosis risk factors (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in these patients have shown that they commonly suffer from vitamin D deficiency [9][10][11]. Low 25(OH)D levels have been associated with atherosclerosis and endothelial dysfunction in patients with end stage renal disease and on hemodialysis [12] and increased 90-day mortality in patients on hemodialysis [11]. Furthermore, in patients with CKD 2-5, the 25(OH)D level is an independent predictor of disease progression and mortality [10;13].…”
Section: 1mentioning
confidence: 99%